ASPECTOS INSTITUCIONAIS E OUTORGA DE ÁGUAS SUBTERRÂNEAS PARA USO INDUSTRIAL NO BAIXO CURSO DO RIO PARAÍBA - Borba Vilar Guimarães, Patricia; da Costa Medeiros, Paulo; Luna Barbosa, Dayse; Rios Ribeiro, Márcia Maria (Águas Subterrâneas, 2008)
Indisponível